Wolność opanowana, czyli pełne wykorzystanie wszystkich funkcji controllingu - Nowicki, Piotr (The Freedom of Control: the Full Use of All Functions of Controlling, 2008)
This article focuses on controlling as a management tool in health care institutions, whose need has been created by current situation in health care institutions. Current processes of restracturizations and adjustment to the markets rules of functioning cannot omit the most difficult area of medicine, that is the question of adjusting medical personnel to the economic situation of health care units. The need for tools that enable health care entities to achieve permanent benefits comes from the fact that the most public health care institutions fail to manage their personnel efficiently. The tool that will help health care entities achieve particular economic goals and at the same time change the way their personnel think and work is controlling. This is why it is essential to implement the elements of controlling.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 36, s. 81-92